2022
DOI: 10.31635/ccschem.021.202101428
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Sulfur Atoms into Palladium Catalysts by Reactive Metal–Support Interaction for Selective Hydrogenation

Abstract: Developing highly active and selective catalysts for hydrogenation of nitroarenes, an environmentally benign process to produce industrially important aniline intermediates, is highly desired but still challenging. Pd catalysts are generally recognized as active but nonselective catalysts for this important reaction. Here we report an effective strategy to greatly improve the selectivity of Pd catalysts based on the reactive metalsupport interaction, by which the sulfur atoms doped in the carbon supports are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Upon further increasing the temperature, alloying between the oxide overlayer and the metal might take place . This process was described as reactive MSIs (RMSIs), attracting broad interest in a number of catalytic reactions. …”
Section: Introductionmentioning
confidence: 99%
“…Upon further increasing the temperature, alloying between the oxide overlayer and the metal might take place . This process was described as reactive MSIs (RMSIs), attracting broad interest in a number of catalytic reactions. …”
Section: Introductionmentioning
confidence: 99%
“…Compared to classical SMSI, the RMSI phenomenon is rarer in carbon materials because the light elements on the surface of carbon vaporize at high temperatures and do not enter the metal to form metal–light element compounds, so RMSI phenomena cannot be observed. It was not until 2020 that RMSI in carbon materials applied to hydrogenation reactions was reported where the researchers found that during the pyrolysis process the S element in the support was embedded into the lattice of Pd, and Pd 4 S intermetallic compounds were formed by simply loading Pd onto the S–C support . As shown in Figure c, the Pd source was anchored onto a preprepared S–C support using the initial wet impregnation method.…”
Section: Characterization Of the Multi Heteroatom Coordination Enviro...mentioning
confidence: 99%
“…It was not until 2020 that RMSI in carbon materials applied to hydrogenation reactions was reported where the researchers found that during the pyrolysis process the S element in the support was embedded into the lattice of Pd, and Pd 4 S intermetallic compounds were formed by simply loading Pd onto the S−C support. 73 As shown in Figure 2c, the Pd source was anchored onto a preprepared S−C support using the initial wet impregnation method. At low temperature, it was found that only one single peak (1.8 Å) corresponding to the Pd−S bond was found in k 2 -weighted FT-EXAFS.…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation
“…An interesting RMSI was found recently in SÀ C supported Pd catalysts, in which the sulfur atoms doped in the carbon supports were extracted out and reacted with Pd [37] to form crystalline Pd 4 S nanoparticle catalysts (Figure 4a). [48] The temperature-dependent structural evolution process of the SÀ C supported Pt catalyst was elucidated with the help of spectroscopic and electron microscopy characterizations. At the low temperature of 300 °C, the Pd species began to react with S atoms that were extracted out from SÀ C supports to form loosely assembled Pd x S nanoclusters with exclusive PdÀ S x configuration.…”
Section: Reactive Metal-support Interactionmentioning
confidence: 99%